Предмет: Математика,
автор: angelinka0740
(2x-3)^2-4x^2=0 как получилось там 12?
Ответы
Автор ответа:
0
не получится тут 12.Если ты про ответ.
(2x-3)^2-4x^2=0
по правилу (a-b)^2=a^3-2ab+b^2
(2x)^2-2*2x*3+3^2-4x^2=0
4x^2-12x(получилось из -2*2х*3) +9-4x^2=0
-12x+9=0
-12x=-9
x=9/12
x=3/4=0.75
(2x-3)^2-4x^2=0
по правилу (a-b)^2=a^3-2ab+b^2
(2x)^2-2*2x*3+3^2-4x^2=0
4x^2-12x(получилось из -2*2х*3) +9-4x^2=0
-12x+9=0
-12x=-9
x=9/12
x=3/4=0.75
Автор ответа:
0
вот там 12 откуда взялось?
Похожие вопросы
Предмет: Химия,
автор: LuciferMoon
Предмет: Информатика,
автор: vikstar555
Предмет: Математика,
автор: demyanenkoviktoria
Предмет: Алгебра,
автор: мегамегамега89
Предмет: Математика,
автор: ЛИЦЕИ